(untitled) (Oratio Directa, 2024)
The increase in stunting rates in the results of the tri-monthly data collection in South Central Timor (TTS) Regency, East Nusa Tenggara Province, from 13,441 to 13,488 in December 2024 raises fundamental questions regarding the factors causing the increase. This qualitative study uses stakeholder-perception analysis, a critical paradigm, and perception theory. The study concludes that the increase in stunting rates in TTS is influenced by parenting patterns, unwanted pregnancies, low education and awareness of following doctors' recommendations, biological and environmental factors, and insufficient family support. Leadership factors and convergent work that have not been maximized are the dominant factors that make stunting rates difficult to reduce in the regency.